Identification of Marketing Strategies Influencing Consumers’ Perception of Healthy Food Products and Triggering Purchasing Decisions - Miquel Vidal, María; Castellano-Tejedor, Carmina (Businesses, 2022)
(1) Background: Marketing and advertising strategies for food products are very diverse and have a differential effect on consumers’ behaviours and attitudes towards products. (2) Objectives: To examine the influence of point-of-purchase (PoP) marketing and advertising strategies and the promotion of products employing opinion leaders (celebrities) on the healthy perception of pre-packaged food and buying behaviour of young consumers. (3) Methods: Online survey (N = 130) of 18–31 years old participants. (4) Results: “Price” was the most influential factor when purchasing a snack (66.2%), although “salt and macronutrient content” had a major influence on females (x2(1,N=129) = 14.02, p < 0.001). Participants with low or no weight satisfaction were more prone to consider “low fat” (x2(1,N=130) = 5.02, p = 0.025) and chose “green” as the most suitable colour for healthy snack packaging. Male celebrities were more picked by males than female participants (x2(1,N=129) = 6.41, p = 0.011). (4) Conclusion: Using green packaging, nutritional claims related to low-calorie intakes or accentuating salt and macronutrient content, and using opinion leaders with whom consumers can relate to, were the most influential factors in fostering a healthy perception of pre-packaged food products. These results highlight the need for policies to limit marketing strategies to avoid misleading consumers’ opinion of a product as healthy when it is not.